2019
DOI: 10.1038/s41598-019-55336-y
|View full text |Cite
|
Sign up to set email alerts
|

Tempo and mode of allopatric divergence in the weakly electric fish Sternopygus dariensis in the Isthmus of Panama

Abstract: Spatial isolation is one of the main drivers of allopatric speciation, but the extent to which spatially-segregated populations accumulate genetic differences relevant to speciation is not always clear. We used data from ultraconserved elements (UCEs) and whole mitochondrial genomes (i.e., mitogenomes) to explore genetic variation among allopatric populations of the weakly electric fish Sternopygus dariensis across the Isthmus of Panama. We found strong genetic divergence between eastern and western population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 84 publications
3
15
0
Order By: Relevance
“…Whittaker's index of β diversity also showed high species turn-over across sites (0.87). Similarly, our rarefaction/extrapolation analyses showed variation in species richness across sites: Frijoles (52), Frijolito (27), Trinidad (22) and Indio (22). However, the most striking pattern was a lack of saturation in the The data show the number of successfully barcoded individuals (Ind.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Whittaker's index of β diversity also showed high species turn-over across sites (0.87). Similarly, our rarefaction/extrapolation analyses showed variation in species richness across sites: Frijoles (52), Frijolito (27), Trinidad (22) and Indio (22). However, the most striking pattern was a lack of saturation in the The data show the number of successfully barcoded individuals (Ind.…”
Section: Resultssupporting
confidence: 64%
“…Typically, diversification in freshwater organisms is marked by a strong geographic signature, where genetic divergence is facilitated by spatial isolation among populations [26,27]. However, the contribution of geographic isolation to the diversification of Neotropical freshwater macroinvertebrates has received little attention to date [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, only 15 of the 426 unique haplotypes reported by Múrria et al [26] overlapped with haplotypes found here. Typically, diversification in freshwater organisms is marked by a strong geographic signature, where genetic divergence is facilitated by spatial isolation among populations [27,28]. However, the contribution of geographic isolation to diversification of Neotropical freshwater macroinvertebrates has received little attention to date [26].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other freshwater taxa [27,28], spatial isolation is likely a major factor driving diversification in macroinvertebrates, but few studies have tested this expectation [26,29,30]. In particular, Murria et al [26] found high frequency of unique haplotypes associated with geographical distance across watersheds in Panama.…”
Section: Introductionmentioning
confidence: 99%